Modified polyether-ether-ketone material, electrode frame, electrolysis equipment, preparation method and application
By using modified polyether ether ketone materials to prepare the pole frame of alkaline electrolytic equipment, the problems of large weight, complex processing and easy corrosion of traditional metal sheet pole frames are solved, and the effect of lightweight, simplified processing and improved service life is achieved.
Patent Information
- Application Number
- CN202411836366.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-11
AI Technical Summary
In the existing alkaline electrolytic hydrogen production equipment, the metal plate pole frame is large in weight, complex in processing, and is prone to corrosion, resulting in a shortened service life of the equipment and a reduced electrolytic efficiency.
Using modified polyether ether ketone materials, the electrode frame is prepared by blending polyether ether ketone PEEK, glass fibers and nanooxides, and injection molding process to reduce weight, simplify the processing process, and improve corrosion resistance.
It realizes lightweighting of the pole frame, simplifies the installation and maintenance process, improves the sealing and service life of the equipment, avoids corrosion problems, and improves the stability and reliability of the electrolytic equipment.
Smart Images

Figure CN119798955A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a modified polyetheretherketone material, an electrode frame, an electrolytic device, a preparation method and an application thereof. Background Art
[0002] At present, most of the plates, frames and bipolar plates for industrial alkaline water electrolysis are made of metal plates as the basic raw materials through precision machining processes. However, this manufacturing method has a series of significant problems: First, due to the physical properties of the metal plates themselves, the plates, frames and bipolar plates are often bulky and heavy, which not only increases the difficulty of transportation and installation of the equipment, but also increases the production cost. Secondly, the processing of metal plates is complicated and cumbersome, and requires fine processing through multiple steps, which further prolongs the production cycle and increases the technical difficulty.
[0003] In addition, these pole frames are designed with flow holes for the circulation of alkali solution. During long-term use, due to the strong corrosiveness of alkali solution, the metal pole frames are very prone to corrosion. Corrosion not only leads to the gradual destruction of the pole frame structure, but also reduces the smoothness of gas and liquid transportation in the flow channel, which greatly reduces the electrolysis efficiency. More seriously, the corrosion problem will accelerate the aging process of the electrolytic cell and severely shorten its service life, thus posing a serious threat to the stability and reliability of the entire electrolysis system. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a modified polyetheretherketone material, pole frame, electrolysis equipment, preparation method and application. The modified polymer material of the present invention is used to prepare a pole frame for hydrogen production by alkaline water electrolysis, which can reduce the weight of the traditional alkaline water hydrogen production electrolyzer, simplify the installation and maintenance process, improve the assembly efficiency of the alkaline water hydrogen production electrolyzer, ensure the sealing of the alkaline water hydrogen production electrolyzer during operation, and is not easily corroded, which can increase the service life of the pole frame. The present invention specifically includes the following contents:
[0005] The first aspect of the present invention protects a modified polyetheretherketone material, comprising the following components in weight: 70-100 parts of polyetheretherketone PEEK, 30-50 parts of glass fiber, and 1-10 parts of nano oxide.
[0006] Furthermore, the nano-oxide is one or more of nano-magnesium oxide, nano-zinc oxide, nano-zirconium oxide, and nano-aluminum oxide.
[0007] Furthermore, the nano-oxide is nano-zirconium oxide.
[0008] Furthermore, the glass fiber is a modified glass fiber; and / or the length of the glass fiber is 3-5 mm; and / or the diameter of the glass fiber is 3-15 μm; and / or the diameter of the nano-oxide is 80-120 nm.
[0009] Furthermore, its fracture stress is ≥120MPa, fracture strain is ≥2.5%, compression strength is ≥219.6MPa, and the tensile strength loss rate in an alkaline environment is <1%, and the compressive strength loss rate is <5.89%.
[0010] The second aspect of the present invention protects a method for preparing the modified polyetheretherketone material, comprising the following steps:
[0011] (1) blending polyetheretherketone (PEEK) powder and nano oxide powder to obtain a blended powder;
[0012] (2) adding glass fiber to the blended powder to obtain a mixture;
[0013] (3) Post-processing the mixture to obtain the modified polyetheretherketone material.
[0014] Furthermore, the nano oxide powder is pretreated before blending in step (1), and the pretreatment method is: vacuum drying the nano oxide at a temperature of 110-160° C. for 7-13 hours.
[0015] Furthermore, the blending method in step (1) is: placing polyetheretherketone PEEK powder and nano oxide powder in a liquid medium, stirring and mixing, and separating after the mixing to obtain the blended powder.
[0016] Furthermore, the liquid medium is an organic solvent.
[0017] Furthermore, the organic solvent is one or more of anhydrous ethanol, acetone, and propyl acetate.
[0018] Furthermore, the glass fiber in step (2) is a modified glass fiber, and the preparation method of the modified glass fiber is: immersing the glass fiber in a modification solution containing a coupling agent.
[0019] Furthermore, the mass ratio of the coupling agent to the solvent in the modified solution containing the coupling agent is (1-6):(94-99); and / or the coupling agent is a silane coupling agent; and / or the solvent of the modified solution is ethanol; and / or the immersion temperature is 50-90°C and the time is 6-10h.
[0020] Furthermore, the silane coupling agent is KH550 and / or KH560.
[0021] Furthermore, the specific preparation method of the modified glass fiber is: after the glass fiber is subjected to high temperature treatment or acid treatment to remove surface impurities, it is placed in a modification solution containing a coupling agent, and after it is immersed for a period of time, the solid-liquid separation and drying are carried out to obtain the modified glass fiber.
[0022] Furthermore, the high temperature treatment temperature is 200-400°C and the time is 0.5-2h; and / or the acid treatment process is: pickling the glass fiber with an acid solution for 10-30min, and the acid solution is one or more of hydrochloric acid solution, nitric acid solution, and sulfuric acid solution.
[0023] Furthermore, after adding the glass fiber to the blended powder in step (2), mixing is required, and the mixing is carried out in a mixer or an internal mixer. During the mixing, the rotation speed of the mixer or the internal mixer is ≥1000 r / h.
[0024] Furthermore, the post-treatment in step (3) includes extrusion granulation, and the extrusion temperature is 330-400°C.
[0025] The third aspect of the present invention protects a pole frame prepared by using the modified polyetheretherketone material.
[0026] The fourth aspect of the present invention protects a method for preparing a pole frame, wherein the modified polyetheretherketone material is injection molded, and after the injection molding is completed, the sample is taken out, and after the sample is cooled to room temperature, the sharp edges of the surface are deburred using sandpaper or other tools to finally obtain the pole frame.
[0027] Furthermore, the mold is preheated to 170-200°C before injection molding; and / or, the injection molding is completed by an injection molding machine, and the barrel temperature of the injection molding machine is set in sections, the root temperature of the barrel is 345-365°C, the middle temperature is 360-390°C, the front temperature is 360-390°C, and the nozzle temperature is set to 375-385°C; and / or, the injection pressure of the injection molding is 8.5-10.5MPa, the holding pressure is 7.5-9.5MPa, and the back pressure is 0.5-1.5MPa.
[0028] A fifth aspect of the present invention protects an electrolytic device having the pole frame described above.
[0029] The sixth aspect of the present invention protects the use of the electrolysis device in producing hydrogen by alkaline water electrolysis.
[0030] Beneficial effects of the present invention:
[0031] (1) The present invention uses glass fiber and nano-oxide modified polyetheretherketone material, and accurately defines the content of each component in the material. The modified polyetheretherketone material of the present invention has a fracture stress of ≥120MPa, a fracture strain of ≥2.5%, a compression strength of ≥219.6MPa, a tensile strength loss rate of <1% and a compressive strength loss rate of <5.89% in an alkaline environment, which can fully meet the application requirements of industrial alkaline water electrolysis equipment.
[0032] (2) The present invention adopts modified polyetheretherketone material to replace traditional metal material to prepare the pole frame, which greatly reduces the weight of the pole plate. Moreover, compared with metal material, modified polyetheretherketone material can be injection molded in one time, with lower requirements on processing temperature and processing equipment, simpler preparation process, lower manufacturing cost, and guaranteed processing accuracy. Moreover, polyetheretherketone material is a special polymer material with physical and chemical properties such as high temperature resistance and chemical corrosion resistance, which can prevent the pole frame from being corroded and increase the service life of the electrolytic equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A comparison chart of TG test results of polymer materials before and after modification provided by the present invention;
[0034] Figure 2 This is a photo of a sample tested for tensile properties in an embodiment of the present invention;
[0035] Figure 3 This is a photo of a sample for compression performance test of an embodiment of the present invention;
[0036] Figure 4 A schematic cross-sectional view of a modified polyetheretherketone material prepared in an embodiment of the present invention;
[0037] Figure 5 This is a photo of a pole frame prepared using the material disclosed in the present invention. DETAILED DESCRIPTION
[0038] The following is combined with Figure 1-5 The present invention is described in detail with specific embodiments. The embodiments shown below do not limit the invention described in the claims. In addition, the entire contents of the configurations shown in the following embodiments are not limited to the solutions required as the invention described in the claims.
[0039] A modified polyetheretherketone material comprises 70-100 parts of polyetheretherketone PEEK, 30-50 parts of glass fiber, and 1-10 parts of nano-oxide, wherein the contents of the components are in mass ratio. The nano-oxide is one or more of nano-magnesium oxide, nano-zinc oxide, nano-zirconium oxide, and nano-aluminum oxide, preferably nano-zirconium oxide. The glass fiber is a modified glass fiber; the length of the glass fiber is 3-5 mm; the diameter of the glass fiber is 3-15 μm; and the diameter of the nano-oxide is 80-120 nm. The fracture stress of the modified polyetheretherketone material of the present invention is ≥120 MPa, the fracture strain is ≥2.5%, the compressive strength is ≥219.6 MPa, the tensile strength loss rate in an alkaline environment is <1%, and the compressive strength loss rate is <5.89%.
[0040] The preparation method of the modified polyetheretherketone material of the present invention comprises the following steps:
[0041] (1) vacuum drying the nano oxide at 110-160° C. for 7-13 h, then placing the polyetheretherketone (PEEK) powder and the nano oxide powder in a liquid medium, stirring and mixing, and separating after the mixing to obtain the blended powder; the liquid medium is one or more of anhydrous ethanol, acetone, and propyl acetate;
[0042] (2) Add modified glass fiber to the blended powder, and then mix in a mixer or internal mixer, control the speed of the mixer or internal mixer to be ≥1000r / h during mixing, and obtain a mixture; the preparation method of the modified glass fiber used in this step is: treat the glass fiber at a high temperature of 200-400°C for 0.5-2h or use one or more of hydrochloric acid solution, nitric acid solution, and sulfuric acid solution for pickling for 10-30min, the purpose of high temperature treatment and pickling treatment is to remove surface impurities; immerse the treated glass fiber in an ethanol solution containing KH550 and / or KH560 silane coupling agent, heat in a water bath at 50-90°C for 6-10h, and then separate the solid and liquid, wash, and dry to obtain the modified glass fiber. The mass ratio of coupling agent to solvent in the modified solution containing coupling agent is (1-6): (94-99);
[0043] (3) Extruding and granulating the mixed material, controlling the extrusion temperature to be 330-400° C., to obtain the modified polyetheretherketone material.
[0044] A pole frame prepared using the modified polyetheretherketone material of the present invention, the preparation method of which is as follows: preheat the mold to 170-200°C before injection molding, use an injection molding machine to injection mold the modified polyetheretherketone material, the injection molding machine barrel temperature is set in sections, the barrel root temperature is controlled to be 345-365°C, the middle temperature is 360-390°C, the front temperature is 360-390°C, and the nozzle temperature is set to 375-385°C; and / or, the injection pressure of the injection molding is 8.5-10.5MPa, the holding pressure is 7.5-9.5MPa, and the back pressure is 0.5-1.5MPa. After the injection molding is completed, take out the sample, and after the sample is cooled to room temperature, deburr the sharp edges of its surface to finally obtain the pole frame, see attached Figure 5 The pole frame is installed in an electrolysis device to meet the application requirements of producing hydrogen by alkaline water electrolysis.
[0045] Example 1
[0046] A method for preparing a modified polyetheretherketone material comprises the following steps:
[0047] (1) using 1 mol / L HCl solution to pickle and soak short glass fibers with a length of 3 mm for 30 min, and then washing with deionized water;
[0048] (2) KH550 and anhydrous ethanol were mixed in a mass ratio of 5:95, and then magnetically stirred for 10 minutes to prepare a modifier solution;
[0049] (3) Immerse the acid-washed chopped glass fibers in the prepared modifier solution and react in a constant temperature water bath at 80° C. for 8 h;
[0050] (4) After the reaction in step (3) is completed, the wet glass fiber is washed with deionized water and then placed in an 80° C. forced air drying oven for 12 h to complete the surface modification of the glass fiber;
[0051] (5) placing the nano-zirconia in a vacuum drying oven at 120° C. and vacuum drying for 12 h;
[0052] (6) placing the dried nano-zirconia and polyetheretherketone (PEEK) powder in anhydrous ethanol at a mass ratio of 5:100 and mechanically mixing for 2 h, then separating the solid and liquid, and drying the solid mixture in a drying oven at 80 °C for 15 h;
[0053] (7) The modified glass fiber is mixed with polyetheretherketone (PEEK) and nano-zirconia blended powder using a mixer, the mass ratio of the modified glass fiber to the polyetheretherketone is controlled to be 30:100, the mixer speed is 1200 r / h, and the mixing time is 2 h;
[0054] (8) The modified polyetheretherketone (PEEK) powder after mixing is granulated using an extruder. The extrusion temperature of the molten modified polymer during granulation is 390° C. The diameter of the extruded particles is about 3 mm and the length is about 5 mm.
[0055] (9) Design the injection mold for the mechanical properties test sample, the polymer tensile properties test sample and the compression properties test sample such as Figure 2 and Figure 3 As shown, the molds are merged;
[0056] (10) Using a muffle furnace, heat the mold to 176°C, take it out, and place it at the nozzle position of the injection molding machine;
[0057] (11) Injection molding, and set the parameters in the injection molding process as follows: barrel root temperature is set to 355°C, middle temperature is set to 385°C, front temperature is set to 385°C, nozzle temperature is set to 375°C, injection pressure is 9.5 MPa, holding pressure is 7.5 MPa, back pressure is 0.5-1.5 MPa, and holding time is 8 s;
[0058] (12) After injection molding, take out the sample and wait for the sample to cool to room temperature before using sandpaper or other tools to deburr the sharp edges of the surface.
[0059] Example 2
[0060] A modified polyetheretherketone material comprises 70 parts of polyetheretherketone PEEK, 30 parts of modified glass fibers with a length of 3-5 mm and a diameter of 3 μm, and 1 part of nano-oxide with a diameter of 80 nm, wherein the contents of the components are in mass ratio. The nano-oxide is nano-zirconium oxide.
[0061] The preparation method of the modified polyetheretherketone material comprises the following steps:
[0062] (1) drying the nano oxide under vacuum at 110° C. for 7 h, then placing polyetheretherketone (PEEK) powder and the nano oxide powder in a liquid medium and stirring and mixing them, and separating after mixing to obtain the blended powder; the liquid medium is anhydrous ethanol;
[0063] (2) Add modified glass fiber to the blended powder, and then mix in a mixer, control the mixer speed to be ≥1000r / h during mixing, and obtain a mixture; the preparation method of the modified glass fiber used in this step is: treat the glass fiber at a high temperature of 200°C for 0.5h, and the purpose of high temperature treatment is to remove surface impurities; immerse the treated glass fiber in an ethanol solution containing KH550 silane coupling agent, heat in a water bath at 50°C for 6h, and then separate the solid and liquid, wash, and dry to obtain the modified glass fiber. The mass ratio of the KH550 silane coupling agent to ethanol is 1:99;
[0064] (3) extruding and granulating the mixed material, controlling the extrusion temperature to be 330° C., to obtain the modified polyetheretherketone material;
[0065] (4) The modified polyetheretherketone material is injection molded to obtain a mechanical property test sample. The injection molding process is as follows: the mold is preheated to 170°C before injection molding, and the modified polyetheretherketone material is injection molded using an injection molding machine. The barrel temperature of the injection molding machine is set in a segmented manner, and the barrel root temperature is controlled to be 345°C, the middle temperature is 360°C, the front temperature is 360°C, and the nozzle temperature is set to 375°C; the injection pressure of the injection molding is 8.5MPa, the holding pressure is 7.5MPa, and the back pressure is 0.5MPa. After the injection molding is completed, the sample is taken out, and after the sample is cooled to room temperature, the sharp edges of the surface are deburred to finally obtain the test sample.
[0066] Example 3
[0067] A modified polyetheretherketone material comprises 100 parts of polyetheretherketone PEEK, 50 parts of modified glass fiber with a length of 5 mm and a diameter of 15 μm, and 10 parts of nano-oxide with a diameter of 120 nm, wherein the contents of the components are in mass ratio. The nano-oxide is nano-zirconium oxide.
[0068] The preparation method of the modified polyetheretherketone material comprises the following steps:
[0069] (1) drying the nano oxide in vacuum at 160° C. for 13 h, then placing polyetheretherketone (PEEK) powder and the nano oxide powder in a liquid medium and stirring and mixing them, and separating after mixing to obtain the blended powder; the liquid medium is acetone;
[0070] (2) Add modified glass fiber to the blended powder, and then mix in an internal mixer, control the speed of the internal mixer to be ≥1200r / h during mixing, and obtain a mixture; the preparation method of the modified glass fiber used in this step is: treat the glass fiber at 400°C for 2h, the purpose of high temperature treatment is to remove surface impurities; immerse the treated glass fiber in an ethanol solution containing KH560 silane coupling agent, heat in a water bath at 90°C for 10h, and then separate the solid and liquid, wash, and dry to obtain the modified glass fiber. The mass ratio of KH560 silane coupling agent to ethanol is 6:94;
[0071] (3) extruding and granulating the mixed material, controlling the extrusion temperature to 400° C., to obtain the modified polyetheretherketone material;
[0072] (4) The modified polyetheretherketone material is injection molded to obtain a mechanical property test sample. The injection molding process is as follows: the mold is preheated to 200°C before injection molding, and the modified polyetheretherketone material is injection molded using an injection molding machine. The barrel temperature of the injection molding machine is set in a segmented manner, and the barrel root temperature is controlled to be 365°C, the middle temperature is 390°C, the front temperature is 390°C, and the nozzle temperature is set to 385°C; the injection pressure of the injection molding is 10.5MPa, the holding pressure is 9.5MPa, and the back pressure is 1.5MPa. After the injection molding is completed, the sample is taken out, and after the sample is cooled to room temperature, the sharp edges of the surface are deburred to finally obtain the test sample.
[0073] Example 4
[0074] A modified polyetheretherketone material comprises 80 parts of polyetheretherketone PEEK, 45 parts of modified glass fiber with a length of 4 mm and a diameter of 10 μm, and 3 parts of nano-oxide with a diameter of 90 nm, wherein the contents of the components are in mass ratio. The nano-oxide is nano-zirconium oxide.
[0075] The preparation method of the modified polyetheretherketone material comprises the following steps:
[0076] (1) drying the nano oxide under vacuum at 120° C. for 8 h, then placing polyetheretherketone (PEEK) powder and the nano oxide powder in a liquid medium and stirring and mixing them, and separating after mixing to obtain the blended powder; the liquid medium is propyl acetate;
[0077] (2) Add modified glass fiber to the blended powder, and then mix in a mixer or internal mixer, control the speed of the mixer or internal mixer to be ≥1300r / h during mixing, and obtain a mixture; the preparation method of the modified glass fiber used in this step is: use hydrochloric acid solution for pickling treatment for 10 minutes, the purpose of pickling treatment is to remove surface impurities; immerse the treated glass fiber in an ethanol solution containing KH550 and KH560 silane coupling agents, heat in a water bath at 60°C for 7 hours, and then separate the solid and liquid, wash, and dry to obtain the modified glass fiber. The mass ratio of the KH550 and KH560 silane coupling agents to ethanol is 3:98;
[0078] (3) extruding and granulating the mixed material, controlling the extrusion temperature to be 350° C., to obtain the modified polyetheretherketone material;
[0079] (4) The modified polyetheretherketone material is injection molded to obtain a mechanical property test sample. The injection molding process is as follows: the mold is preheated to 180°C before injection molding, and the modified polyetheretherketone material is injection molded using an injection molding machine. The barrel temperature of the injection molding machine is set in a segmented manner, and the barrel root temperature is controlled to be 355°C, the middle temperature is 370°C, the front temperature is 370°C, and the nozzle temperature is set to 380°C; the injection pressure of the injection molding is 9MPa, the holding pressure is 8MPa, and the back pressure is 0.8MPa. After the injection molding is completed, the sample is taken out, and after the sample is cooled to room temperature, the sharp edges of the surface are deburred to finally obtain the test sample.
[0080] Example 5
[0081] A modified polyetheretherketone material comprises 90 parts of polyetheretherketone (PEEK), 40 parts of modified glass fiber with a length of 3.5 mm and a diameter of 5 μm, and 5 parts of nano-oxide with a diameter of 100 nm, wherein the contents of the components are in mass ratio. The nano-oxide is nano-aluminum oxide.
[0082] The preparation method of the modified polyetheretherketone material comprises the following steps:
[0083] (1) drying the nano oxide under vacuum at 140° C. for 11 h, then placing polyetheretherketone (PEEK) powder and the nano oxide powder in a liquid medium, stirring and mixing, and separating after mixing to obtain the blended powder; the liquid medium is a mixture of anhydrous ethanol, acetone, and propyl acetate;
[0084] (2) Add modified glass fiber to the blended powder, and then mix in an internal mixer, control the speed of mixing to ≥1000r / h, and obtain a mixture; the preparation method of the modified glass fiber used in this step is: use a mixed solution of nitric acid solution and sulfuric acid solution to pickle the glass fiber for 30 minutes, the purpose of the pickling treatment is to remove surface impurities; immerse the treated glass fiber in an ethanol solution containing KH560 silane coupling agent, heat in a water bath at 65°C for 9 hours, and then separate the solid and liquid, wash, and dry to obtain the modified glass fiber. The mass ratio of KH560 silane coupling agent to ethanol is 5:95;
[0085] (3) extruding and granulating the mixed material, controlling the extrusion temperature to be 380° C., to obtain the modified polyetheretherketone material;
[0086] (4) The modified polyetheretherketone material is injection molded to obtain a mechanical property test sample. The injection molding process is as follows: the mold is preheated to 185°C before injection molding, and the modified polyetheretherketone material is injection molded using an injection molding machine. The barrel temperature of the injection molding machine is set in sections, and the barrel root temperature is controlled to be 360°C, the middle temperature is 370°C, the front temperature is 380°C, and the nozzle temperature is set to 380°C; the injection pressure of the injection molding is 10MPa, the holding pressure is 9MPa, and the back pressure is 1.0MPa. After the injection molding is completed, the sample is taken out, and after the sample is cooled to room temperature, the sharp edges of the surface are deburred to finally obtain the test sample.
[0087] Comparative Example 1
[0088] The difference between this comparative example and Example 1 is that the modified polyetheretherketone material includes 60 parts of polyetheretherketone PEEK, and other conditions are the same.
[0089] Comparative Example 2
[0090] The difference between this comparative example and Example 1 is that the modified polyetheretherketone material includes 110 parts of polyetheretherketone PEEK, and other conditions are the same.
[0091] Comparative Example 3
[0092] The difference between this comparative example and Example 1 is that the modified polyetheretherketone material includes 20 parts of glass fiber, and other conditions are the same.
[0093] Comparative Example 4
[0094] The difference between this comparative example and Example 1 is that the modified polyetheretherketone material includes 55 parts of glass fiber, and other conditions are the same.
[0095] Comparative Example 5
[0096] The difference between this comparative example and Example 1 is that the modified polyetheretherketone material includes 0.5 parts of nano zirconium oxide, and other conditions are the same.
[0097] Comparative Example 6
[0098] The difference between this comparative example and Example 1 is that the modified polyetheretherketone material includes 15 parts of nano zirconium oxide, and other conditions are the same.
[0099] Comparative Example 7
[0100] The difference between this comparative example and Example 1 is that glass fiber and nano-oxide modifier are not added to the polyetheretherketone material, and other conditions are the same.
[0101] The material prepared in Example 1 and the material prepared in Comparative Example 7 were subjected to TG test. The test results are as follows: Figure 1 As shown, from Figure 1 It can be seen that the weight loss temperature of the PEEK material modified by adding glass fiber and nano-oxide remains unchanged, the weight loss rate is slowed down at high temperature, the weight loss ratio is reduced, and the thermal decomposition resistance is improved.
[0102] The samples obtained from Examples 1-5 of the present invention and Comparative Examples 1-7 were subjected to mechanical property tests. Figure 2 This is a photo of the sample tested for tensile properties; Figure 3 This is a photo of the compression performance test sample; Figure 4 This is a schematic cross-sectional view of a modified polyetheretherketone material prepared in an embodiment of the present invention.
[0103] For tensile samples: the tensile performance test is carried out at room temperature, and the specific method is carried out in accordance with GB / T228.1-2010; the alkali resistance test conditions are: after immersion in 30% KOH solution at 95°C for 720h, the tensile performance test is carried out according to the above method;
[0104] For compression samples: the compression performance test is carried out at room temperature, and the specific method is in accordance with GB / T 1041-2008; the alkali resistance test conditions are: after immersion in 30% KOH solution at 95°C for 720 hours, the compression performance test is carried out according to the above method.
[0105] The mechanical properties test results are shown in Table 2:
[0106] Table 2 Test results of samples of Examples 1-5 and Comparative Examples 1-6
[0107]
[0108]
[0109] It can be seen from the test results in Table 2 that the samples prepared in the embodiments of the present invention have a fracture stress of ≥120MPa, a fracture strain of ≥2.5%, and a compressive strength of ≥219.6MPa. After 720h alkali resistance test, the tensile strength loss rate is <1% (some embodiments even have no loss), and the compressive strength loss rate is <5%. However, the tensile strength and compressive strength of the samples obtained in the comparative examples are significantly worse than those of the samples in the embodiments, and the performance loss of the samples obtained in the comparative examples after alkali treatment is significantly higher than that of the samples prepared in the embodiments.
[0110] The material prepared in the embodiment of the present invention is subsequently processed to obtain an electrode frame, and the electrode frame is applied to an electrolysis device, which can meet the application requirements of industrial alkaline water electrolysis equipment.
[0111] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A modified polyetheretherketone material, characterized in that: The invention comprises the following components in weight: 70-100 parts of polyetheretherketone (PEEK), 30-50 parts of glass fiber and 1-10 parts of nano oxide.
2. A modified polyetheretherketone material according to claim 1, characterized in that: The nano-oxide is one or more of nano-magnesium oxide, nano-zinc oxide, nano-zirconium oxide and nano-aluminum oxide.
3. A modified polyetheretherketone material according to claim 2, characterized in that: The nano oxide is nano zirconium oxide.
4. The modified polyetheretherketone material according to claim 1, characterized in that: The glass fiber is a modified glass fiber; and / or the length of the glass fiber is 3-5 mm; and / or the diameter of the glass fiber is 3-15 μm; and / or the diameter of the nano-oxide is 80-120 nm.
5. The modified polyetheretherketone material according to any one of claims 1 to 4, characterized in that: Its fracture stress is ≥120MPa, fracture strain is ≥2.5%, compression strength is ≥219.6MPa, tensile strength loss rate is <1% and compressive strength loss rate is <5.89% in an alkaline environment.
6. A method for preparing the modified polyetheretherketone material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) blending polyetheretherketone (PEEK) powder and nano oxide powder to obtain a blended powder; (2) adding glass fiber to the blended powder to obtain a mixture; (3) Post-processing the mixture to obtain the modified polyetheretherketone material.
7. The method for preparing a modified polyetheretherketone material according to claim 6, characterized in that: The nano oxide powder is pretreated before blending in step (1), and the pretreatment method is: vacuum drying the nano oxide at a temperature of 110-160° C. for 7-13 hours.
8. The method for preparing a modified polyetheretherketone material according to claim 6, characterized in that: The blending method in step (1) is: placing polyetheretherketone (PEEK) powder and nano-oxide powder in a liquid medium, stirring and mixing them, and separating them after the mixing to obtain the blended powder.
9. The method for preparing a modified polyetheretherketone material according to claim 8, characterized in that: The liquid medium is an organic solvent.
10. The method for preparing a modified polyetheretherketone material according to claim 9, characterized in that: The organic solvent is one or more of anhydrous ethanol, acetone, and propyl acetate.
11. The method for preparing a modified polyetheretherketone material according to claim 6, characterized in that: The glass fiber in step (2) is a modified glass fiber, and the preparation method of the modified glass fiber is: immersing the glass fiber in a modified solution containing a coupling agent.
12. The method for preparing a modified polyetheretherketone material according to claim 11, characterized in that: The mass ratio of the coupling agent to the solvent in the modified solution containing the coupling agent is (1-6):(94-99); and / or the coupling agent is a silane coupling agent; and / or the solvent of the modified solution is ethanol; and / or the immersion temperature is 50-90°C and the time is 6-10h.
13. The method for preparing a modified polyetheretherketone material according to claim 12, characterized in that: The silane coupling agent is KH550 and / or KH560.
14. The method for preparing a modified polyetheretherketone material according to claim 11, characterized in that: The specific preparation method of the modified glass fiber is: after the glass fiber is subjected to high temperature treatment or acid treatment to remove surface impurities, it is placed in a modification solution containing a coupling agent, immersed for a period of time, solid-liquid separation and drying to obtain the modified glass fiber.
15. The method for preparing a modified polyetheretherketone material according to claim 14, characterized in that: The high temperature treatment temperature is 200-400°C and the time is 0.5-2h; and / or the acid treatment process is: using an acid solution to pickle the glass fiber for 10-30min, and the acid solution is one or more of hydrochloric acid solution, nitric acid solution, and sulfuric acid solution.
16. The method for preparing a modified polyetheretherketone material according to claim 6, characterized in that: After adding the glass fiber to the blended powder in step (2), mixing is further performed, and the mixing is performed in a mixer or an internal mixer. During the mixing, the rotation speed of the mixer or the internal mixer is ≥1000 r / h.
17. The method for preparing the modified polyetheretherketone material according to any one of claims 6 to 16, characterized in that: The post-treatment in step (3) includes extrusion granulation, and the extrusion temperature is 330-400°C.
18. A pole frame prepared by using the modified polyetheretherketone material according to any one of claims 1 to 5.
19. A method for preparing a pole frame according to claim 18, characterized in that: The modified polyetheretherketone material is injection molded to obtain the pole frame.
20. A method for preparing a pole frame according to claim 19, characterized in that: The mold is preheated to 170-200°C before injection molding; and / or, the injection molding is completed by an injection molding machine, and the barrel temperature of the injection molding machine is set in sections, the root temperature of the barrel is 345-365°C, the middle temperature is 360-390°C, the front temperature is 360-390°C, and the nozzle temperature is set to 375-385°C; and / or, the injection pressure of the injection molding is 8.5-10.5MPa, the holding pressure is 7.5-9.5MPa, and the back pressure is 0.5-1.5MPa.
21. An electrolysis device having the pole frame according to claim 18.
22. Use of the electrolysis device according to claim 21 in producing hydrogen by alkaline water electrolysis.
Citation Information
Patent Citations
Electrode plate of hydrogen production by water electrolysis and production method
CN102828199A
Nano-modified polyether-ether-ketone material and preparation method thereof
CN104788897A
Polyether-ether-ketone / nanometer zinc oxide / carbon fiber wear-resistant composite material and preparation method thereof, and application of composite material to mechanical polishing of retaining rings
CN106633627A
Efficient and green method for preparing polyether ether ketone composite material reinforced by nano-modified polyether arone sized fiber cloth
WO2024244127A1